Associate Professor, NSS Training College, Ottapalam, Palakkad, Kerala - KAFI, KAJI ABDUL; UDDIN, MD JAMAL; AGARWAL, P.C. (JOURNAL OF INDIAN EDUCATION, 2025)
The effect of concept mapping strategy on learning outcome in Geography of Class IX students was investigated. A quasi-experimental pre-test and post-test control group design was adapted. Two Government-sponsored bengali medium schools in Kolkata were selected randomly. The experimental group (n=40) and the control group (n=40) were assigned randomly. The sample for this study consisted of 80 students of Class IX. The Learning Outcome Test with a reliability coefficient of 0.75 and a validity coefficient of 0.86 developed by the researcher was used for collecting the data. For analysing the data, one-way Analysis of Covariance (ANCOVA) and 2×2 factorial design ANCOVA were employed. The findings of the study showed that the experimental group students achieved higher learning outcome in comparison to the control group students. Further, finding of this study also revealed that there was no significant effect of interaction between treatment and type of family on students’ learning outcome in Geography, when pre-learning outcome was considered as a covariate. Therefore, it can be recommended that concept mapping strategy might be incorporated in teaching-learning of Geography as well as in other school subjects at different grades for enhancing learning outcomes